AFRICAN DANCE AND ITS HISTORICAL TRAJECTORY: INTERFACES WITH MUSEOLOGY - Clotilde Oliveira Pinheiro, Maria (Revista Gênero e Interdisciplinaridade, 2025)
The report analyzes the trajectory of African dance in Tefé, highlighting its cultural influence and its relationship with museology. The study aims to understand how this manifestation remains alive, contributing to the preservation of Afro-descendant identity and its insertion in the educational and museological context. The research adopts a qualitative approach, based on direct observation, interviews and documentary analysis. Based on authors such as Camargo (2013), Garcia and Hass (2006), Oliveira (2007), Barreto (2008), Pessoa (1956) and Moreira (2015), the study discusses dance as intangible heritage and its importance in the construction of cultural identity. The results demonstrate that African dance in Tefé plays a significant role in the valorization of collective memory and in the strengthening of local identity, despite the challenges faced in its preservation. It is concluded that the integration between dance and museology contributes to its continuity, promoting the recognition of this expression as a fundamental element of Afro-Brazilian culture.